TRENDS IN SCORPION DIVERSITY AND RICHNESS IN MOROCCO - ABDELMONAIM, EL HIDAN MOULAY; MEHDI, AIT LAARADIA; EL-MUSTAPHA, LAGHZAOUI; ABDESSAMAD, ELMOURID; OULAID, TOULOUN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
To date, Vachon's study (1952) remains the only synthetic work that has addressed scorpion species and their distribution in North Africa. However, in spite of this important contribution to the description of the Moroccan scorpions, a great biodiversity of this fauna continues to be revealed, especially since revisions of the classical scorpion groups have allowed the description of new species as well as new genera. Thus, the aim of this study is to update the inventory and analyze the distributional pattern of the Moroccan scorpion fauna. A previous list of scorpions from Morocco, is updated, based on a survey conducted during several separate expeditions, and completed by published data. More than 1200 specimens, representing more than 400 point-locality records, were examined for the study. Notes on the ecology and distribution of the scorpions in Morocco are provided. 61 scorpion species in twelve genera of two families (Buthidae and Scorpionidae) are recorded from the area, which presently has the richest scorpion fauna in Northern Africa, if not the Mediterranean basin, and ranks among those with the richest scorpion faunas in the world. The high diversity of scorpions in Morocco is attributed to the heterogeneity of landforms, substrata and habitats in the area. The analysis of species richness points "Hotspots" indicates that most central regions of Morocco contain at least one species of scorpion. The greatest diversity of genera and species occurs central areas. A high endemism characterizes Moroccan scorpion-fauna, with 73% of the species is restricted to Morocco.